2014
DOI: 10.3201/eid2011.131872
|View full text |Cite
|
Sign up to set email alerts
|

Legionnaires’ Disease Incidence and Risk Factors, New York, New York, USA, 2002–2011

Abstract: Living in low-income areas and working in certain occupations may increase risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
113
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(125 citation statements)
references
References 16 publications
4
113
0
8
Order By: Relevance
“…In patients with risk factors (smoking, chronic cardiovascular or respiratory disease, diabetes, alcohol abuse, and immunosuppression), LD is sometimes complicated by more severe disease (cavitation and pleural effusions) [25][26][27]. Jacobson et al [28], in a study of Legionella pneumonia in cancer patients, reported the presence of multilobar pneumonia in 82 % of the patients, bilateral involvement in 80 %, and pleural effusion in 56 % of the patients.…”
Section: Legionella Pneumophilamentioning
confidence: 99%
“…In patients with risk factors (smoking, chronic cardiovascular or respiratory disease, diabetes, alcohol abuse, and immunosuppression), LD is sometimes complicated by more severe disease (cavitation and pleural effusions) [25][26][27]. Jacobson et al [28], in a study of Legionella pneumonia in cancer patients, reported the presence of multilobar pneumonia in 82 % of the patients, bilateral involvement in 80 %, and pleural effusion in 56 % of the patients.…”
Section: Legionella Pneumophilamentioning
confidence: 99%
“…Multiple state public health agencies in the United States have shown people of African descent to represent a disproportionately high number of legionellosis cases. 58, 59 In a nationwide examination of public health data by the Centers for Disease Control (CDC), incidence among this group was substantially higher than for whites. 23 Additionally, residents of low-income neighborhoods in the state of New York have also been shown to have increased odds of contracting legionellosis.…”
Section: Introductionmentioning
confidence: 99%
“…23 Additionally, residents of low-income neighborhoods in the state of New York have also been shown to have increased odds of contracting legionellosis. 59 Further studies will be necessary to determine if these two risk groups are due to medical (comorbidities, limited health care), environmental (low-quality drinking water, premise plumbing deficiencies), or social (smoking rates, high-risk jobs) reasons.…”
Section: Introductionmentioning
confidence: 99%
“…In the USA 8000-18,000 persons are hospitalized for legionellosis each year. In the 2000s, a substantial increase in the number of reported cases was observed (Farnham et al 2014). The average case-fatality rate is 10 % in Europe and 8 % in the USA.…”
Section: Introductionmentioning
confidence: 98%
“…Recognized host risk factors for LD include smoking, diabetes, older age (>50 years), having a chronic underlying disease with or without an associated immunodeficiency, and receipt of a transplant or chemotherapy. Environmental risk factors associated with legionellosis outbreaks are travel, proximity to cooling towers, whirpool spas, decorative fountains, residence in a health care facility (Farnham et al 2014). In Europe, about 6000 Legionnaires' disease cases are noted annually (Beaute et al 2013).…”
Section: Introductionmentioning
confidence: 98%